2021
DOI: 10.1109/access.2021.3052415
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Navigation Assistants for Blind and Visually Impaired People: A Systematic Review

Abstract: Over the last few decades, the development in the field of navigation and routing devices has become a hindering task for the researchers to develop smart and intelligent guiding mechanism at indoor and outdoor locations for blind and visually impaired people (BVIPs). The existing research need to be analysed from a historical perception including early research on the first electronic travel aids to the use of modern artificial vision models for the navigation of BVIPs. Diverse approaches such as: e-cane or g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 209 publications
0
15
0
Order By: Relevance
“…A systematic review of outdoor pedestrian navigation systems for visually impaired people reported in literature from 2015 to 2020 is presented in [49]; even though the system analysis is very accurate leading to an interesting hierarchical taxonomy, the scope of this review is limited to one type of users moving in urban environments only. A systematic review of solutions for blind and visuallyimpaired people is presented in [87]: 191 most relevant articles published between 2011 and 2020 have been selected from different digital libraries and analyzed according to different dimensions, such as approaches and technologies proposed for navigation, hardware components used for obstacle avoidance, and adopted performance metrics. This is the most recent and extended review available in literature, but it pays attention only to visual disabilities.…”
Section: Related Workmentioning
confidence: 99%
“…A systematic review of outdoor pedestrian navigation systems for visually impaired people reported in literature from 2015 to 2020 is presented in [49]; even though the system analysis is very accurate leading to an interesting hierarchical taxonomy, the scope of this review is limited to one type of users moving in urban environments only. A systematic review of solutions for blind and visuallyimpaired people is presented in [87]: 191 most relevant articles published between 2011 and 2020 have been selected from different digital libraries and analyzed according to different dimensions, such as approaches and technologies proposed for navigation, hardware components used for obstacle avoidance, and adopted performance metrics. This is the most recent and extended review available in literature, but it pays attention only to visual disabilities.…”
Section: Related Workmentioning
confidence: 99%
“…Different types of walking assistants are being used by visually impaired individuals to enable them to move around and perform their day-to-day activities. A recent systematic review was performed to analyze the navigation assistant systems used for blind and visually impaired people [ 7 ]. In this review, studies proposing navigation assistants were classified according to the different design approaches used, technology/tools adopted to implement these systems, the mechanisms/applications followed and the parameters considered to ensure the applicability and the reliability of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Some of those articles were read when preparing this paper, to understand the different ways this subject has been addressed in the past. In their articles, Bhowmick and Hazarika [4] and Khan et al [5] provided detailed descriptions of their research methodologies, highlighting the connections between the different fields pertaining to assistive technologies for BVIP. They spotted the most frequent keywords found in the papers they analyzed and their common sources, and stressed the trends of research.…”
Section: Introductionmentioning
confidence: 99%